Doomscrolling, Monitoring and Avoiding: News Use in COVID-19 Pandemic Lockdown. (3rd October 2021) - Ytre-Arne, Brita; Moe, Hallvard
ABSTRACT: This paper analyzes news use during the COVID-19 pandemic, asking how people balance between conflicting needs for information and disconnection in an extraordinary situation. We analyze empirical data from a qualitative questionnaire study of Norwegian media users conducted in March–April 2020, a period of early pandemic lockdown. The acute lockdown context accentuated intensified monitoring of constantly updated news streams, and perceptions of news use as immersive and emotionally draining, as captured in the notion of "doomscrolling". To cope with feelings of being scared or overwhelmed, even the most connected citizens deliberately and intermittingly avoided news. Discussing these findings in light of the debate on news avoidance in journalism studies, we argue for the relevance of understanding news avoidance as a situational strategy. We conclude that the concept of news avoidance remains relevant to qualitatively understand a human experience of wanting to avoid news in particular contexts. Our analysis further outlines interconnections between different practices of pandemic news use, including a research-based conceptualization of doomscrolling as a phenomenon.